The Neuropeptide α-Calcitonin Gene-Related Peptide as the Mediator of Beneficial Effects of Exercise in the Cardiovascular System - Skaria, Tom; Vogel, Johannes (Frontiers in Physiology, 2022)
Regular physical activity exerts cardiovascular protective effects in healthy individuals and those with chronic cardiovascular diseases. Exercise is accompanied by an increased plasma concentration of α-calcitonin gene-related peptide (αCGRP), a 37-amino acid peptide with vasodilatory effects and causative roles in migraine. Moreover, mouse models revealed that loss of αCGRP disrupts physiological adaption of the cardiovascular system to exercise in normotension and aggravates cardiovascular impairment in primary chronic hypertension, both can be reversed by αCGRP administration. This suggests that αCGRP agonists could be a therapeutic option to mediate the cardiovascular protective effects of exercise in clinical setting where exercise is not possible or contraindicated. Of note, FDA has recently approved αCGRP antagonists for migraine prophylaxis therapy, however, the cardiovascular safety of long-term anti-CGRP therapy in individuals with cardiovascular diseases has yet to be established. Current evidence from preclinical models suggests that chronic αCGRP antagonism may abolish the cardiovascular protective effects of exercise in both normotension and chronic hypertension.